Ad-hoc Networks and Wireless - Garcia Pineda, M (Springer, 2015)
This book constitutes the refereed proceedings of six workshops collocated with the 13th International Conference on Ad-Hoc Networks and Wireless, ADHOC-NOW Workshops 2014, held in Benidorm, Spain, in June 2014. The 25 revised full papers presented were carefully reviewed and selected from 59 submissions. The papers address the following topics: emerging technologies for smart devices; marine sensors and systems; multimedia wireless ad hoc networks; security in ad hoc networks; smart sensor protocols and algorithms; wireless sensor, actuator and robot networks.